Gas exchange parameters in leaves and ears of winter wheat Tricitum aestivum L. and its productivity under fungicide control conditions - Joanna K. Jarmołkowicz; Jacek Olszewski (Acta Agrobotanica, 2012)
A research experiment was conducted in which rates of photosynthesis and transpiration were measured in leaves and ears of two winter wheat varieties grown under fungicide control conditions and without fungicide control. A LI-COR 6400 portable gas exchange system was used in the investigations. In most cases the fungicide Juwel was shown to have no effect on the gas exchange processes, whereas the other of the fungicidal agents applied - Swing - significantly decreased the gas exchange rates measured. Measurements of gas exchange parameters in ears showed that the intensity of gas exchange was low, in particular at the later stage of ear development. But the applied fungicide caused higher release of CO2 into the atmosphere than its uptake. Furthermore, the applied fungicides were found to significantly increase grain yield compared to the control treatment, both in the first and second year of the study. Among the tested varieties, 'Nutka' was characterized by higher productivity, in spite of lower 1000 kernel weight. However, this cultivar developed longer ears with a larger amount of grains.